2006
DOI: 10.1080/08035250500437499
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in children diagnosed with asthma, diabetes, juvenile chronic arthritis or short stature

Abstract: The Swedish version of the CHQ is a reliable and valid instrument. Furthermore, it is recommended to ask children themselves about their health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 15 publications
3
17
1
1
Order By: Relevance
“…While parents of short children commonly report problems of cognitive development, personality, self-esteem or social relations, their children do so only sporadically. Although some studies assessed behavior and adaptation by both self- and proxy report [26, 38], the correlation between child- and parent-rated HrQoL has yet to be systematically examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While parents of short children commonly report problems of cognitive development, personality, self-esteem or social relations, their children do so only sporadically. Although some studies assessed behavior and adaptation by both self- and proxy report [26, 38], the correlation between child- and parent-rated HrQoL has yet to be systematically examined.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of patients with SS reported higher HrQoL in physical function, bodily pain and general health perceptions compared to groups with chronic illness. Ratings on the dimensions of self-esteem and behavior did not differ from patients with asthma or diabetes [26]. …”
Section: Hrqol Research In Children and Adolescents With Iss And Ghd mentioning
confidence: 99%
“…Some studies suggest that JIA does not negatively affect HRQOL or psychosocial functioning (6 -9), whereas other studies report that children with JIA have a lower HRQOL compared to healthy children (10 -16) and compared to children with other chronic health conditions (17,18). Although a large number of studies have assessed HRQOL in children with JIA, only a few studies focused on predictors of HRQOL in children with JIA.…”
Section: Introductionmentioning
confidence: 99%
“…We identified nine papers that looked at QoL in other growth-related conditions treated with growth hormone. [36][37][38][39][40][41][42][43][44] Again these presented a variety of results, but only limited evidence that there is a strong link between QoL and final height gain. Several of the studies called for further research into the links between QoL and short stature and the tool with which this is evaluated.…”
Section: Resultsmentioning
confidence: 99%